What's missing from this picture? Ethical, legal, and practical challenges for autonomous-vehicle data-recorders - Ten Holter, C; Kunze, L; Pattinson, J-A; Salvini, P; Attias, J; Jirotka, M (Association for Computing Machinery, 2024)
Many sources propose that Autonomous Vehicles (AVs) could offer societal benefits in the future. Although such claims frequently relate to safety, AVs will undoubtedly also create new types of incidents and accidents. Data related to failure or accidents will therefore be a fundamental requirement for ensuring safety, accountability and public trust. Regulations and standards are being developed for equipping AVs with data recorders, also known as Black Boxes. These devices can log different types of parameters related to the vehicle status and collect large volumes of data relating to the vehicle and the surrounding environment. Although data retrieval is vital to understanding the causes of an accident and contributing to ongoing safety developments, there can be ethical risks as well as legal, social and political implications related to collection, storage, processing, access and use of data. In this work, we took a responsible innovation approach to these questions, seeking to establish the current practice with regard to technology, people, and institutions involved with AV data recorders, evaluate the usefulness of present regulations for defining safety-critical scenarios, and identify gaps that could have significant consequences further down the line. We close with recommendations for future work and practice